Micromechanics evaluation of equivalent temperature-dependent stiffness of graphene-reinforced shape memory polymer nanocomposites - Usama Umer; Mustufa Haider Abidi; Zeyad Almutairi; Mohammed A. El-Meligy (Results in Engineering, 2024)
Effective stiffness of shape memory polymer (SMP) nanocomposites filled with graphene nanoplatelets (GNPs) is analyzed at various temperatures using an efficient micromechanical scheme. Three microstructural features, including aggregation and non-flatness shape of graphene, and GNP/SMP interphase are incorporated. It is found that addition of GNPs can enhance the temperature-dependent stiffness of SMP nanocomposites. The nanocomposite stiffness is more improved by (I) increasing the volume fraction, (II) increasing the length (or width) and (III) decreasing the thickness of uniformly dispersed GNPs. Also, an effective way to remarkably augment the nanocomposite stiffness is suggested to be alignment of the GNPs into the SMP matrix. However, the aggregated state and non-flatness configuration of GNPs act as two lowering factors of SMP nanocomposite stiffness. From mechanical viewpoint on designing a SMP nanocomposite, the interfacial zone should be as stiff and thick as possible. It is observed at very low volume fraction that the non-flatness structure and interfacial zone should be included in the modeling to give better predictions as compared with experiments. At high volume fraction, the GNP aggregation in addition to those two factors should be reflected in the analysis to encompass a more realistic micromechanical scheme.